Character Education Implementation: A Students’ Perception - Husnuzhan, Husnuzhan; Safitri, Dian (Universitas Negeri Padang, 2024)
Character education becomes a crucial part in educational system in Indonesia. The problems face by late generations which can degrade their character make it more important. The Integration of Character Education with Project-Based Learning (PjBL) in Paragraph Writing class become one of many ways to fix students problem. This research was a quantitative-research which employed questionnaire as the measurement toll. There were 18 items distributed to the samples with 2 different aspects. There were 125 students from academic year 2022/2023 which enrolled Paragraph Writing class in English Department, Universitas Negeri Padang participated as the samples of this research. Students were given a treatment by the lecturer for a whole semester and the researcher found the samples’ perceptions. To find the students’ perceptions, Likert Scale 1 to 4 was used in this study. This study found that the integration of Character Education and PjBL shows very positive result to increase students’ character.